KEDOKTERAN – Vol. 11 No. 1 Januari 2021 Universitas Batam Page 31 MOTHER'S KNOWLEDGE ABOUT TODDLER NUTRITION PUSKESMAS BOTANIA, BATAM CITY - Muhammad Dezarino; Yusmahenry Galindra (Universitas Batam, 2021)
Nutritional problems are a complex problem not only due to powerlessness or economic inadequacy, but also regarding knowledge, attitudes and behavior. The number of nutritional status at Botania Puskesmas in 2016, the prevalence of underfives with malnutrition and malnutrition is 583 (17.2%) out of 10,712 children under five. The purpose of this study was to know the knowledge of mothers about toddler nutrition. Method : This study used a descriptive study of the population of all mothers who have children aged 1-5 years, the sampling technique used was accidental sampling. The research results were analyzed by Univariate. Result : Research Results Maternal knowledge about toddler nutrition at Puskesmas Botania, Batam City in 2017 with good knowledge respondents as many as 20 people (50%) as large as respondents who have sufficient knowledge. Conclusion :. Maternal knowledge about toddler nutrition at Puskesmas Botania, Batam City in 2017 with 20 respondents (50%) good knowledge as large as respondents who had sufficient knowledge.